Injury Patterns of Drivers and Other Vehicle Occupants in the Banja Luka Region (Bosnia and Herzegovina) - NediÄ‡, D; Lipovac, K; Karan, Å½ (International Journal of Medical Toxicology and Forensic Medicine, 2015)
Background: Traffic traumatism in Bosnia and Herzegovina has not been given adequate attention and there is a lack of serious research on this problem. Motor vehicle occupants represent a significant number of fatalities on local roads. The aim of this study was to identify particular risk groups of traffic participants and determine the differences in injuring due to the position of the vehicle. Methods: Study included 400 injured and fatally injured occupants among 2009-2013 in Banja Luka. We analyzed of demographic and injury characteristics, cause of death and alcohol intoxication of drivers. Data are presented numerically and in percentages, statistically analyzed. Results: Men account for nearly 3/4 of the total number of deaths and over 95% of dead drivers. Nearly two-thirds of victims were aged 15-44 years, and one third of injured were in the third decade of life. Drivers more often had AIS3+ injuries of head, chest, abdomen and AIS2+ injuries of thoracic spine and lower extremities. More often drivers and front passengers had AIS3+ chest injuries, while the back seat occupants had AIS3+ head injuries. There was a positive correlation between age and frequency of AIS3+ chest injuries and AIS2+ spinal injuries. The most common cause of death were head (41%) and chest injuries (33.3%). Nearly 3/4 of injured persons were died at the scene of accident or during transport to the nearest health care facility. Nearly 60% of killed drivers had legally prohibited BAC (> 0.3 g/kg). Conclusion: Men in motor vehicles more often die in traffic accidents, and a particularly vulnerable category is young male drivers. Seat belts using on domestic routes is dissatisfactory and additional efforts are required.